Faktor-Faktor Yang Membuat Maraknya Penggunaan Bahasa Asing Maupun Bahasa Gaul Dikalangan Anak Muda - Annisa Muty Nur Ami; Cindy Dwiana Putri; Fitriani Lubis; Nadia Indah Lestari; Sendari Felida Nababan; Shandy Hadrianus Saragih; Silvia Diva Sari (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research was carried out with the aim of studying and researching the factors that cause the increasing use of slang among young people. This research method uses a qualitative descriptive approach and applies the literature study method. There are several factors that cause the widespread use of Prokem language or slang, namely the result of the rise of slang language appearing on sites that are often accessed by young people, interference or mixing of two languages, environmental factors, and finally the role of the media which also plays a role. be one of the factors.Keyword: Language, factors, young people